A molecular signature for the G6PC3/SLC37A2/SLC37A4 interactors in glioblastoma disease progression and in the acquisition of a brain cancer stem cell phenotype - Torabidastgerdooei, Sima; Roy, Marie-Eve; Annabi, Borhane (Frontiers in Endocrinology, 2023)
Background: Glycogen plays an important role in glucose homeostasis and contributes to key functions related to brain cancer cell survival in glioblastoma multiforme (GBM) disease progression. Such adaptive molecular mechanism is dependent on the glycogenolytic pathway and intracellular glucose-6-phosphate (G6P) sensing by brain cancer cells residing within those highly hypoxic tumors. The involvement of components of the glucose-6-phosphatase (G6Pase) system remains however elusive. Objective: We questioned the gene expression levels of components of the G6Pase system in GBM tissues and their functional impact in the control of the invasive and brain cancer stem cells (CSC) phenotypes. Methods: In silico analysis of transcript levels in GBM tumor tissues was done by GEPIA. Total RNA was extracted and gene expression of G6PC1-3 as well as of SLC37A1-4 members analyzed by qPCR in four human brain cancer cell lines and from clinically annotated brain tumor cDNA arrays. Transient siRNAmediated gene silencing was used to assess the impact of TGF--induced epithelial-tomesenchymal transition (EMT) and cell chemotaxis. Three-dimensional (3D) neurosphere cultures were generated to recapitulate the brain CSC phenotype. Results: Higher expression in G6PC3, SLC37A2, and SLC37A4 was found in GBM tumor tissues in comparison to low-grade glioma and healthy tissue. The expression of these genes was also found elevated in established human U87, U251, U118, and U138 GBM cell models compared to human HepG2 hepatoma cells. SLC37A4/G6PC3, but not SLC37A2, levels were induced in 3D CD133/SOX2-positive U87 neurospheres when compared to 2D monolayers. Silencing of SLC37A4/G6PC3 altered TGF-βinduced EMT biomarker SNAIL and cell chemotaxis. Conclusion: Two members of the G6Pase system, G6PC3 and SLC37A4, associate with GBM disease progression and regulate the metabolic reprogramming of an invasive and CSC phenotype. Such molecular signature may